Soccer match play as an important component of the power-training stimulus in Premier League players - Morgans, R.; Di Michele, R.; Drust, B. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Competitive match play is a dominant component of the physical load completed by soccer players in a training microcycle. Characterizing the temporal disruption in homeostasis that follows exercise may provide some insight on the potential for match play to elicit an adaptive response. Methods: Countermovement-jump (CMJ) performance was characterized 3 d postmatch for 15 outfield players from an English Premier League soccer team (age 25.8±4.1 y, stature 1.78±0.08 m, body mass: 71.7±9.1 kg) across a season. These players were classified as either starters (n=9) or nonstarters (n=6), according to their average individual playing time (more or less than 60 min/match). Linear mixed models were used to investigate the influence of indicators of match activity (total distance covered [TD] and high-intensity running distance [HI]) on CMJ height and peak power (PP). Results: Starting players covered much greater TD (ES=1.5) and HI (ES=1.4) than nonstarters. Furthermore, there was a possible positive effect of HI on CMJ height and PP. This relationship suggests that an additional 0.6 km of HI would increase CMJ height and PP by slightly more than the smallest-worthwhile-change values of 0.6 cm and 1.0 W/kg, respectively. This small yet practically relevant increase in performance may suggest that match play, more specifically the intense activities that are associated with the match, provides a physiological stimulus for neuromuscular adaptation. Conclusions: These data may have implications for the preparation of soccer squads, especially the training requirements of starting and nonstarting players.